Personality traits influence the effectiveness of hypomania checklist-32 in screening for bipolar disorder - Wang, Qiang; Sui, Aiping; Gong, Lin; Chattun, Mohammad Ridwan; Han, Ruichen; Cao, Qiuyun; Shen, Diwen; Zhang, Yuzhe; Zhao, Peng (Frontiers in Psychiatry, 2022)
Background: It is clinically challenging to distinguish bipolar disorder (BD) from major depressive disorder (MDD) in the early stages. While the Hypomania Checklist-32 (HCL-32) is a proper auxiliary tool that is useful to differentiate between BD and MDD, there is currently no standard cut-off value. The variations in HCL-32 cut-off values could potentially be influenced by personality traits. Therefore, the aim of this study is to explore the effect of personality traits on the screening performance of HCL-32. Methods: In this retrospective cross-sectional study, 168 patients with BD or MDD were evaluated with the Eysenck Personality Questionnaire (EPQ) and HCL-32. The associations between demographic data, diagnosis and clinical rating scales were analyzed. Results: Diagnosis was not associated with extraversion but was related to neuroticism. HCL-32 scores in typical extraverted patients were higher in contrast to atypical extraverted patients. The best cut-off value for BD recognition of typical and atypical extraversion groups were 15 and 12.5, respectively. In patients with MDD, HCL-32 score of typical neuroticism was higher than the atypical type, but there was no difference in patients with BD. In typical neuroticism, there was no difference in HCL-32 scores between patients with MDD and BD. But among atypical neurotic patients, HCL-32 scores of BD were higher compared to MDD, with a cut-off value of 14.5. Limitations: This study had a small sample size. Conclusions：HCL-32 scores were affected by personality traits, with higher scores for typical extraversion and neuroticism. Clinicians should also consider the patients’ personality traits when referring to HCL-32 scores, so as to increase the recognition rate of BD and eliminate false positives.